Cerebral Tuberculomas Mimicking A Brain Tumor: Report of Two Cases - Gill, Arwinder Singh; Firdaus, Muhammad; Sugiarto, Yosafat Kurniawan; Rayhani, Farilaila; Andriani, Rini; Faried, Ahmad (http://dharmais.co.id/, 2024)
Introduction : Cerebral tuberculoma, a seldom encountered and severe manifestation of tuberculosis (TB), arises from the dissemination of Mycobacterium tuberculosis through the bloodstream. Its symptoms and radiological characteristics lack specificity, often resulting in diagnostic errors. Management predominantly involves medical intervention, with the treatment duration for cerebral tuberculoma ranging from 6 to 36 months. In specific instances, surgical intervention may be advised. Case presentation: We reported two cases of cerebral tuberculoma occurring in patients who presented with seizures, with space-occupying lesions evident on magnetic resonance imaging of the brain. There were no symptoms of concurrent extra cranial TB. Surgery was performed on both of the cases and anti-TB treatment began as soon as the diagnosis was made with corticosteroid as adjuvant treatment. Conclusion: : A combination of clinical, radiological, and histopathological examination is needed to confirm the diagnosis and determine the appropriate therapy. If ICP is increased as a result of the lesion and medical therapy has failed, surgical excision is required.